The crucial role of Erk2 in demyelinating inflammation in the central nervous system. Issue 1 (December 2016) - Okazaki, Rentaro; Doi, Toru; Hayakawa, Kentaro; Morioka, Kazuhito; Imamura, Osamu; Takishima, Kunio; Hamanoue, Makoto; Sawada, Yasuhiro; Nagao, Motoshi; Tanaka, Sakae; Ogata, Toru
Abstract Background Brain inflammation is a crucial component of demyelinating diseases such as multiple sclerosis. Although the initiation of inflammatory processes by the production of cytokines and chemokines by immune cells is well characterized, the processes of inflammatory aggravation of demyelinating diseases remain obscure. Here, we examined the contribution of Erk2, one of the isoforms of the extracellular signal-regulated kinase, to demyelinating inflammation. Methods We used the cuprizone-induced demyelinating mouse model. To examine the role of Erk2, we used Nestin-cre-driven Erk2-deficient mice. We also established primary culture of microglia or astrocytes in order to reveal the crosstalk between two cell types and to determine the downstream cascades of Erk2 in astrocytes. Results First, we found that Erk is especially activated in astrocytes within the corpus callosum before the peak of demyelination (at 4 weeks after the start of cuprizone feeding). Then, we found that in our model, genetic ablation of Erk2 from neural cells markedly preserved myelin structure and motor function as measured by the rota-rod test. While the initial activation of microglia was not altered in Erk2-deficient mice, these mice showed reduced expression of inflammatory mediators at 3–4 model weeks. Furthermore, the subsequent inflammatory glial responses, characterized by accumulation of microglia and reactive astrocytes, were significantly attenuated in Erk2-deficient mice. These data indicate that Erk2 in astrocytes is involved in augmentation of inflammation and gliosis. We also found that activated, cultured microglia could induce Erk2 activation in cultured astrocytes and subsequent production of inflammatory mediators such as Ccl-2. Conclusions Our results suggest that Erk2 activation in astrocytes plays a crucial role in aggravating demyelinating inflammation by inducing inflammatory mediators and gliosis. Thus, therapies targeting Erk2 function in glial cells may be a promising approach to the treatment of distinct demyelinating diseases.